Stem cell therapy for central nervous system disorders: Metabolic interactions between transplanted cells and local microenvironments - Stacey A. Sakowski; Kevin S. Chen (Neurobiology of Disease, 2022)
Stem cell therapy is a promising and rapidly advancing treatment strategy for a multitude of neurologic disorders. Yet, while early phase clinical trials are being pursued in many disorders, the mechanism of action often remains unclear. One important potential mechanism by which stem cells provide neuroprotection is through metabolic signaling with diseased neurons, glia, and other cell types in the nervous system microenvironment. Early studies exploring such interactions report normalization of glucose metabolism, induction of protective mitochondrial genes, and even interactions with supportive neurovasculature. Local metabolic conditions also impact stem cell biology, which can have a large impact on transplant viability and efficacy. Epigenetic changes that occur in the donor prior to collection of stem cells, and even during in vitro culture conditions, may have effects on stem cell biology that are carried into the host upon stem cell transplantation. Transplanted stem cells also face potentially toxic metabolic microenvironments at the targeted transplant site. Novel approaches for metabolically “preconditioning” stem cells prior to transplant harness metabolic machinery to optimize stem cell survival upon transplant. Ultimately, an improved understanding of the metabolic cross-talk between implanted stem cells and the local nervous system environment, in both disease and injury states, will increase the likelihood of success in translating stem cell therapy to early trials in neurological disease.